The Asset Portfolios of Older Australian Households - Hildebrand, V.A.; Cobb-Clark, D (My University, 2010)
This paper investigates whether there is evidence that households adjust their asset portfolios just prior to retirement in order to maximise their eligibility for a means-tested public pension. To this end, we take advantage of recently available, detailed micro data for a nationally-representative sample of Australian households to estimate a system of asset equations that are constrained to add up to net worth. Our results provide little evidence that in 2006 healthy households or couples were responding to the incentives embedded in the asset and income tests used to determine Australian Age Pension eligibility by reallocating their assets. While there are some significant differences in asset portfolios associated with having an income near the income threshold, being of pensionable age and being in poor health, these differences are often only marginally significant, are not robust across time, and are not clearly consistent with the incentives inherent in the Australian Age Pension eligibility rules. Any behavioral response to the incentives inherent in the Age Pension means test in 2006 appears to be predominately concentrated among single pensioners who are in poor health. In 2002 there is also evidence that healthy households above pension age held significantly more wealth in their homes than did otherwise similar younger households, perhaps suggesting some reduction in the incentives to reallocate assets over time.
Australian Social Policy Journal
Keywords: Ageing; Finance -- Assets; Finance; Income, wealth and finances; Finance; Ageing; Assets; Income, wealth and finance